HUBUNGAN KONSUMSI GULA TAMBAHAN, LEMAK, AKTIVITAS FISIK, DAN DURASI TIDUR DENGAN STATUS GIZI LEBIH REMAJA PUTRI DI SMAN 12 JAKARTA PADA MASA PANDEMI COVID19 - Diah Rosanti (2021)
According to Riskesdas survey in 2018, in Jakarta Special Region of Indonesia, the prevalency of less physical activity among adolescents between 15-19 years old reaches 63,08%, the prevalency of high-fat food consumption is 51,9% dan high-sugar food consumption is 55,14% in age between 15-19 years old. Lack of sleep is also known to cause weigh-gain among adolescents. Method: This study was hold between December 2020 until February 2021. This research study was taken place in 12 Senior High School Jakarta. This observational with cross-sectional-approached study used 63 female youth between 15-18 years old. The added-sugar intake data was collected using Semi-Quantitative Food Frequency Questionnaire, the fat intake was collected using Food Recall 3x24 hours, physical activity level was measured with PAL questionnaire from WHO, and PSQI (Pittsburgh Sleep Quality Index) for the sleep duration. Due to pandemic situation, the research are conducted online. All data were analyzed by Chi Square SPSS version 16. Results: Half of the participants are obese (58,3%).There is no correlation between sugar intake, fat intake, and physical activity with obesity. But there is a correlation between sleep duration and obesity among female adolescents (p-value: 0,008)